2000
DOI: 10.1530/eje.0.1420524
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide and aldosterone secretions, and atrial natriuretic peptide-binding sites in kidneys and adrenal glands of pregnant and fetal rats in late gestation in response to a high-salt diet

Abstract: Objective: This study aimed at determining, in the term pregnant rat, whether maternal and fetal plasma atrial natriuretic peptide (ANP) concentrations were modified in response to an oral sodium load, and to investigate whether any changes in plasma concentrations were able to modify the density and affinity of the different ANP-binding site subtypes in maternal and fetal kidneys and adrenal glands. Methods: Pregnant rats kept in metabolic cages were divided into two groups. The normal sodium diet group had f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
(105 reference statements)
3
10
0
2
Order By: Relevance
“…On the opposite, high-sodium intake reduces the activity of this system (12). As expected, we observed that sodium supplements of 0.9 or 1.8% decreased the activity of RAAS, as measured by PRA and aldosterone levels.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…On the opposite, high-sodium intake reduces the activity of this system (12). As expected, we observed that sodium supplements of 0.9 or 1.8% decreased the activity of RAAS, as measured by PRA and aldosterone levels.…”
Section: Discussionsupporting
confidence: 85%
“…However, this maneuver did not modify the decrease in blood pressure observed during rat pregnancy (31). On the opposing side, highsodium intake during pregnancy induces reduction in PRA and aldosterone (12). Such alteration of activity of RAAS can provide a valuable avenue to modify the reduction of blood pressure associated with the end of pregnancy in the rat.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, results from rat dams consuming large amounts salt have shown that although the plasma sodium of the mother may not change, the plasma sodium of the offspring may increase because of the immaturity of their kidney (Deloof et al, 2000). Hence, our third hypothesis is that a high-salt diet or saltbush will increase plasma concentrations of chloride and keep sodium the same in ewes but increase plasma concentrations of both chloride and sodium in lambs at birth.…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, it is well known that an increased sodium intake, like that of many other mineral and nutrient requirements, occurs during pregnancy, [23][24][25][26]. Barelare and Ritcher (1938) [27] for example, demonstrated for the first time that, when pregnant dams have access to a rich sodium source, the total sodium intake increases between 60-98% compared with pregnant rats who have access to water only.…”
mentioning
confidence: 99%